Категорії «чесність/нечесність» у весільному обрядовому комплексі (на прикладах македонської весільної обрядовості) - Петреська, В. (Народна творчість та етнографія, 2009)
The categories chastity/non-chastity have a high place in the traditional wedding ritual complex. This primarily regards the bride, because besides her social change she acquires with the wedding (the change of residence), the sexual change as a more important one is accentuated with her. We have seen that in the non-verbal communication (first of all the rituals «bringing two young people together» and «celebrating the chastity of the bride», with the ritual procedures - showing the mark on the sheet, the sweet brandy, fetching water or informing about the non-chastity), as well as in the verbal communication (open declaration about the chastity/non-chastity by the bride herself or the mother-in-law). These two rituals «bringing two young people together» and «celebrating the chastity of the bride», where these categories are fully expressed, gives me the right to think that they were the key ones in the wedding, with which the bride will be completely accepted or not accepted into the new family. This is confirmed by the whole wedding ritual complex (costumes, songs). Our assertion is confirmed by modern researches which show that the sweet brandy still represents one of the major rituals of the wedding. Although today this ritual does not have its original meaning and function, but it is transformed in a ritual whose essential function is entertainment, its existence tells us that in the past it was a key ritual. But, the preservation of the sweet brandy, with the dramatic erotic scenes performed by women, in contemporary conditions even in a more accentuated form, gives me the right to consider that it was the key ritual in the past, which would permitted or not permitted at all, the bride to be fully accepted into the new family.